2008
DOI: 10.1002/jbm.b.31126
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylation of dental zirconia surfaces: Characterization and bonding potential

Abstract: Bioinert zirconia surfaces exhibit a low chemical bonding potential to resin-based luting agents. The aim was to hydroxylate dental zirconia surfaces and to examine tensile bond strength using commercial luting agents. The measured bond strength was compared with established mechanical conditioning techniques. Five acidic and one alkaline hydroxylation pretreatments were applied and compared with air abrasion and tribochemical silica coating. For the chemical characterization of hydroxyl groups and hydroxyl va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 23 publications
5
61
0
6
Order By: Relevance
“…[3][4][5][6] Despite these advantages, it is hard to obtain a proper bonding to other substrates because of its hydrophobic surface. 7,8 Several studies have shown that unmodified surfaces display low bond strength and eventually leads to adhesive failure, [9][10][11] so there is a need to intensify surface properties of these ceramics to reach an effective bonding. 12 These surface modifications are based on roughening the surface and increasing its wettability.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Despite these advantages, it is hard to obtain a proper bonding to other substrates because of its hydrophobic surface. 7,8 Several studies have shown that unmodified surfaces display low bond strength and eventually leads to adhesive failure, [9][10][11] so there is a need to intensify surface properties of these ceramics to reach an effective bonding. 12 These surface modifications are based on roughening the surface and increasing its wettability.…”
Section: Introductionmentioning
confidence: 99%
“…Although the loss of retention has never been a topic of interest with Y-TZP restorations (because it has never been reported), efforts have been undertaken to establish ways to achieve a reliable bond between Y-TZP crowns and luting agents. [22][23][24][25][26][27][28][29][30][31][32][33][34] Comparatively, data from a literature review 11 showed a 2.8% loss of retention rate in all-ceramic systems (except for zirconia) after five years, while for a metal-ceramic system the loss of retention rate decreases to 0.7% after 10 years. 35 Thus, the effective bond strength between the substrate and ceramic plays an important role in enhancing the longevity of restorative treatments 25,29,[36][37][38][39][40] and in preventing microleakage.…”
Section: Introductionmentioning
confidence: 99%
“…Acidic treated with Piranha solution also created hydroxylation at Zirconia surface, which strongly increased the bond strength between zircon and resin cements, such as Multilink (Ivoclar Vivadent). However, it didn't improve MDP-containing resin cement, Panavia F2.0 (Kuraray) (Lohbauer et al, 2008). The laser treatments, such as erbium: yttriumaluminum-garnet (Er: YAG) Er: YAG and neodymium:: yttrium-aluminum-garnet (Nd: YAG) laser, significantly increased the bond strength of Zirconia, while CO (2) laser treatment was less effective for improving Zirconia bonding (Akin et al, 2011;Paranhos et al, 2011).…”
Section: Non-silica-based Ceramics (Zirconia)mentioning
confidence: 99%